Teoria fundamentada na sobrevivência da pessoa travesti e transexual à ideação suicida - Silva, Glauber Weder dos Santos (2021)
Introduction: the suicide, a complex phenomenon, is a serious public health problem and suicidal ideation has been identified in the literature as the best predictor to prevent a suicide attempt, particularly among travestis and transsexuals. Discovering strategies, mechanisms and devices to overcome suicidal ideation among travestis and transsexuals constitute, in itself, an important step to enhance their lives. Objective: to understand how travestis and transsexuals deal with suicidal ideation. Methods: multiphase and mixed methods study. In the first phase, a study was developed with concomitant data triangulation in the period from 2015 to 2016. In the cross-sectional phase, 58 travestis and transsexuals from nongovernmental organizations in Rio Grande do Norte/Brazil participated. The prevalence of suicidal ideation was verified through The Beck Scale for Suicide Ideation (BSSI) and received descriptive statistical treatment. In the qualitative stage, 24 travestis and transsexuals with suicidal ideation in the previous group participated. The meanings attributed to suicide were described and analyzed through thematic content analysis. Quantitative and qualitative data were analyzed as they were similar, complementary or opposite. Later, in the second phase, between 2018 and 2021, the procedures of the Grounded Theory were used in the way proposed by Strauss and Corbin and the theoretical framework of Symbolic Interactionism. Twenty-four travestis and transsexuals with suicidal ideation in the previous phase were eligible for the first sample group. From the hypotheses raised in the analysis process and by the principle of theoretical saturation, the study enrolled 18 participants divided into five sample groups: first - nine travestis and transsexuals with suicidal ideation in the first phase; second - three travestis and transgender social leaders/activists; third - two family members from the first group; fourth - two travestis and transsexuals undergoing hormone therapy; fifth - two health professionals from the transgender health clinic in Rio Grande do Norte, Brazil. Data were collected through in-depth interviews from 2016 to 2021, with simultaneous data collection and analysis, with open, axial and selective coding procedures and construction of diagrams, memos and consequential matrices. A theoretical-explanatory model of the identified phenomenon was elaborated. Study approved by CEP/UFRN in two phases: opinions No. 1.314.559 of 11/09/2015 and No. 3187.452 of 03/08/2019, respectively. Results: the prevalence of suicidal ideation among participants was 41.4% (n=24) (CI% 41.3 -54.51%). From the descriptive statistical analysis in line with the codification, classification and categorization process, a joint-display was elaborated with three phases: 1st phase "He arrived and put me under his arms": the grandparents as the family nucleus, "What am I doing here in this life?": elaborating feelings and reasons for committing suicide and BSSI item "reasons for suicide attempt"; 2nd phase "Having a second of courage you go and do it": experiencing suicide and BSSI items “previous suicide attempt, wish to die and active suicide attempt”; 3rd phase "They will never accept our transsexuality": experiencing transphobia in the family and society, "Friend and mother's shoulder": overcoming suicidal behavior and BSSI item "attitude towards ideation". Seeking to understand how transvestites and transsexuals deal with suicidal ideation, three components, eleven themes, forty concepts, 115 categories and 799 codes emerged in the theorizing procedures that integrate the central category (substantive theory) - "Acceptance of the transvestite and transsexual person ”: 1st component: the family grant (conditions) – living in the family (non-acceptance by the parents, the father violating the transgender child, suffering from family rejection vs. maternal acceptance, acceptance of grandparents and family understanding about transsexuality); 2nd component: Sociality (actions/interactions) – social activism (feeling the responsibility of activism vs. identifying with trans activism, becoming an activist, overcoming suicidal ideation in activism and acting for trans health); social networks (rejecting trans people, raping trans people, living abusive relationships vs. supporting trans people); the school (rejecting trans people vs. studying for a living); the world of work (not accessing the job market, being stigmatized in the job market vs. being accepted in the job market, surviving with the help of work); health services (being rejected from health services vs. receiving specialized health care); health professionals (attitudinal negativity vs. offering comprehensive care); 3rd component: Self-assertion (results/consequences) – self-regulation (self-mutilation); suicidal behavior (surging suicidal ideation, attempting suicide vs. eliminating suicidal ideation); hormonization (frustrated by the lack of support, selfhormonization, consequences of misuse vs. helping to accept oneself, achieving authenticity, receiving professional support, and possibly not using); and being who you are (not conforming to the skin you inhabit, psychic suffering vs. understanding being trans and becoming who you are). Final considerations: The theoretical-methodological articulation between the data showed that the survival of travestis and transsexuals is based on the acceptance of the trans person in the scenarios they occupy, integrating the family, the social context and the self-affirmation of who they are. The convergences and divergences of the results are considered to support the thesis: the survival of the travestis and transsexual person to suicidal ideation is possible when the family and society accept them and provide them with social identity and conditions of access to the world of work and reach of policies that grant them autonomy over their bodies, the libertarian expression of their gender identity and the right to be who they really are.